Hydrological characteristics of lakes in the eastern part of the Broknes Peninsula, Larsemann Hills, East Antarctica - A. S. Boronina; S. V. Popov; G. V. Pryakhina (Лëд и снег)
Broknes Peninsula (the area of the Progress station, Larsemann Hills, Princess Elisabeth Land, East Antarctica) is characterized by the presence of well developed hydrographic network consisting of reservoirs located not only in the bedrock, but also inside the glacier thickness and on its surface. As a rule, most of them are dammed by natural snowice weirs, which are often destroyed during the Antarctic summer. As a result of this process, glacial water outburst may occur. In the course of the summer season of the 63‑th Russian  Antarctic Expedition (RAE) intensive hydrological field observations were carried out for identification and comprehensive investigation of potentially outburstprone reservoirs located in close proximity to Russian and foreign stations and field bases (area of the  Progress station and the field base Law-Racovita). The works included: the organization of temporary pile and depth-stick water gauge stations, mapping positions of the shoreline of lakes (reservoirs), bathymetric surveys of them, as well as field hydro-chemical express analyses. Based on the results of the level measurement, it was found that most of the lakes of the oasis are characterized by a sharp drop in the height of the water surface level associated with the breakthroughs. In particular, the authors witnessed the breakthrough of the Discussion Lake, which occurred on January 22, 2018. This resulted in decrease of the water level by 0.95 m. Based on the data of the bathymetric surveys, the morphometric (hydrometric) characteristics of the lakes were calculated and detailed grids (regular net of rectangular matrices, in the nodes of which some effective values of the mapped values are located) were formed for the following numerical modeling of hypothetical and real breakthroughs of water bodies and construction of estimated hydrographs.